Analysis of Biomass Briquettes Made from Rubber Seed Shells and Acacia Sawdust with Variation in Material Composition Percentage - Alfian, Devia Gahana Cindi; Sindhu, I Gede Pande Naraya; Paundra, Fajar; Silitonga, Dicky Januarizky; Nugraha, Andhyka Tyaz (invotek, 2025)
Indonesia is reducing reliance on fossil fuels by expanding renewable energy, including biomass from rubber-plantation residues and acacia wood. This study evaluates briquettes made from rubber seed shell (RSS) and acacia sawdust (AWS) using 10% tapioca binder, a compaction pressure of 50 kgf cm⁻², and drying at 100 °C for 3 h. Three compositions (RSS:AWS, %wt) were tested: A (50:50), B (70:30), and C (80:20). The best performance was obtained for C (80:20), with moisture 7.40%, volatile matter 9.56%, ash 4.47%, fixed carbon 85.95%, HHV 6,716.88 cal g⁻¹ (28.10 MJ kg⁻¹), and burn rate 0.10 g min⁻¹. All compositions satisfied SNI 01-6235-2000 limits for HHV (≥ 5,000 cal g⁻¹), VM (≤ 15%), and ash (≤ 8%); the moisture criterion (≤ 8%) was met by B and C. For context, SNI 1683:2021 (wood charcoal, not briquettes) imposes stricter thresholds; under these, C is closest to First-Quality ranges, while A and B fall short for several parameters. Overall, increasing the RSS (char) fraction produced briquettes with lower moisture and VM, higher fixed carbon and HHV, and steadier combustion suitable for household fuel.